PEMBENTUKAN AKHLAK DALAM PENDIDIKAN MELALUI SANKSI EDUKATIF (Kajian Literasi Terhadap Pembelajaran) - Murtadha, Murtadha; Muammar, Muammar (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2024)
In fact, efforts to form morals through various educational institutions, both formal, informal and non-formal, as well as through various methods, continue to be carried out and developed. This shows that morals need to be formed, nurtured, educated and accustomed to. Meanwhile, apart from education, other factors that support the formation of a person's morals are parents and their environment. Without the guidance of parents and their environment, a child's behavior will not be directed towards the good. In the world of education, sanctions are adjusted to the severity or lightness of the violation. Sanctions are a form of affection from educators towards students. The hope is that after giving sanctions, students will not carry out their actions again. So that order and discipline are created. From the continuous application of educational sanctions, good morals will be formed for these children. These morals are not only useful in the school environment, but when the student has graduated from school, he will be accepted by the surrounding community.